Management of common bile duct stones with a biliary endoprosthesis. Report on 40 cases. Issue 10 (October 1992) - Peters, R; Macmathuna, P; Lombard, M; Karani, J; Westaby, D
Abstract : Endoscopic placement of a biliary endoprosthesis has been proposed for the management of choledocholithiasis when stone extraction is difficult or considered hazardous. Over a two year period this approach was used in 40 such patients. There were 24 women and 16 men with a median age of 76 years. In seven patients with severe cholangitis no attempt was made to extract the stones. Twenty three (57.5%) patients underwent a sphincterotomy and four (10%) needle knife papillotomy. The endoprosthesis insertion was considered a temporary measure in 13 (32.5%) patients and definitive treatment in 27 (67.5%). Bile duct drainage was established in all patients. Early complications occurred in six patients (15%), but were without sequelae. Late complications developed in eight (20%) of the patients and included biliary colic (four), cholangitis (three), and cholecystitis (one). Two patients (one cholangitis and one cholecystitis) died as a consequence of the complication. Only patients without a sphincterotomy developed cholangitis. A total of eight patients (20%) underwent surgery (one as an emergency) and nine a repeat endoscopic retrograde cholangio pancreatography (two as an emergency) to clear the duct. The remaining 23 patients are asymptomatic at a median of 13 months (range five to 24 months). Biliary endoprosthesis insertion for choledocholithiasis is an important alternative means of establishing drainage in selected cases, and is probably the optimum method of management for the elderly and or debilitated patients with previous cholecystectomy. Caution must be exercised, however, in patients with an in situ gall bladder.